JURIDICIAL REVIEW IMPLEMENTATION OF LAND REGISTRATION ACCORDING TO GOVERNMENT REGULATION NO. 18 OF 2021 CONCERNING MANAGEMENT RIGHTS, LAND RIGHTS, FLAT UNITS AND LAND REGISTRATION - Lalu Nuzul Indrawan; Arba; Aris Munandar (Transpublika Publisher, 2022)
There are differences from the implementation of land registration related to the announcement of land registration. The Government Regulation should be implemented properly, but in fact in the field the regulation still does not provide certainty. In order to provide legal certainty to the community with the issuance of Government Regulation Number 18 of 2021. The purpose of this study was to determine and analyze the legal arrangements for land registration according to Government Regulation No. 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration, and to identify and analyze Government Regulation No. 24 of 1997 concerning Land Registration with Government Regulation No. 18 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration, and to find out and analyze the legal consequences of changes to Government Regulation Number 24 of 1997 after the enactment of Government Regulation Number 18 of 2021. This research is normative legal research. Approach methods used in this research are Legislative Approach, Conceptual Approach, Comparative Approach; and analytical approach. Based on the research findings, it can be concluded that Regulations which is the legal basis that is still valid for Government Regulation Number 18 of 2021 concerning Management Rights of Land Rights, Flats and Land Registration Units which are still being carried out without first revoking Government Regulation Number 24 of 1997 concerning Land Registration which has a period of The announcement is different between the two Government Regulations, namely, with the principle of Lex Posterior Derogat Legi Priori.